Sekuritisasi Radiasi Nuklir Chernobyl di Wilayah Regional Uni Eropa - Firyalmira, Farah; Putranti, Ika Riswanti (Journal of International Relations, 2020)
Environmental issues has become an important issues in the international world nowadays, even in some countries environmental issues as equivalent to political issues. After the end of the Second World War in 1945, apparently the issue of nuclear began to be popular to be discussed. The issue of nuclear attracted the attention of the European Union, Then Euratom Community was formed which had a focus on improving the security of nuclear energy development. The Chernobyl accident that occurred in 1986 in Ukraine was one of the worst nuclear accidents in history. Seeing this accident, the European Union then began to participate in the Chernobyl nuclear radiation handling activities in the area around Ukraine. Handling activities undertaken by the European Union focus on improving the security of nuclear energy development. At first these handling activities were only aimed at victims' countries around Ukraine, but then along with the development of the European Union era, they began to implement these handling activities in their regional areas. According to research conducted by UNSCEAR there is no nuclear radiation contamination in the European Union region. The purpose of this study is to find out the reasons behind the change in the attitude of the European Union in responding to the issue of Chernobyl nuclear radiation in its regional region. In analyzing this process, this research uses securitization theory with qualitative methods, literature study in data collection, and process tracing data analysis methods. The results showed that the change in the attitude of the European Union on the issue of Chernobyl nuclear radiation is a form of EU securitization to prevent the adverse ef ects of radiation that has entered into its regional territory to become more widespread and detrimental.